The Effect of Effective Microorganism (EM) Inclusion to the Setting Time of Microbed Cement Paste - Noorli, Ismail; Hamidah, Mohd Saman; Mohd Faizal, Md Jaafar; Siti Radziah, Abdullah (EDP Sciences, 2017)
The inclusion of Effective Microorganism (EM) lengthen the setting time of microbed cement paste with respect to the control cement paste. However, the investigation on the influence of EM ingredients to the setting time was not performed yet in the earlier study. Therefore, the test of X-Ray Diffraction (XRD) was performed on the EM product used in order to determine their ingredients. Further examination was carried out to analyse the pore characteristics in examining the effect of the pore size distribution to the setting time of microbed cement paste. Potassium Chloride (KCl) was detected in EM liquid using XRD test. It can be concluded, the ingredient of EM which is consist of the molasses influenced the setting time of microbed cement paste. The hardening rate of microbed cement paste was effected by the presence of KCl. The pore size of microbed cement paste recorded the lower pore volume (mL/g) with respect to the control cement paste. The larger intrusion of mercury was recorded at smaller pore diameter in microbed cement paste while control cement paste occupied at the bigger pore diameter. The microbed cement paste (16.5%) recorded the smaller porosity than cement paste without EM (20.3%). The smaller cement pore effects the delayed setting time of microbed cement.